Selectivity in Organizational Rule Violations - Lehman, David W.; Ramanujam, Rangaraj (Academy of Management Review, 2009)
Organizational rule violations are more likely when performance falls below aspiration levels. We propose that such violations are systematically selective and that this selectivity emerges during the problemistic search for solutions to the performance shortfall. During this search, contextual conditions (structural secrecy and coupling between violations and outcomes) and characteristics of rules (enforceability, procedural emphasis, and connectedness) direct attention and shape risk perceptions. Consequently, some rules are more likely to be violated than others.